Instagram Social Media Content Management @Beraucoal.id through CSR Program in Building Corporate Image in 2023 - Benny Cahya Ramadhan; Aziz, Zuhdan (Jogjakarta Communication Conference (JCC), 2025)
Mining activities often receive mixed reviews from the public, depending on the benefits felt and the negative impacts caused. In 2023, PT Berau Coal was considered successful in implementing various company initiatives, such as providing educational facilities, community empowerment programs, environmental conservation, humanitarian assistance, and health programs, which led to it winning a number of awards related to the Corporate Social Responsibility (CSR) program. A well-managed CSR program plays an important role in creating a positive perception and building and maintaining a company's image in the eyes of the public. As one of the largest companies in the mining sector operating in Berau Regency, East Kalimantan, PT Berau Coal utilizes the Instagram platform @beraucoal.id as an effective means of communication. In managing its content, Instagram @beraucoal.id has characteristics that reflect the company's identity through consistent visual design and the right choice of colors. This study aims to analyze the management of Instagram social media content @beraucoal.id through the CSR program in building the company's image in 2023. A qualitative approach with a case study method and the theory of four media management functions according to Morissan (Planning, Organizing, Actuating, and Controlling) were used in this study, with data obtained through documentation and interviews with related parties in the management of the company's social media. The results of the study indicate that the Instagram account @beraucoal.id has carried out the stages of content production management which include planning, organizing, implementing, and supervising. In addition, the management of Instagram content @beraucoal.id also applies the SOME perspective (Share, Optimize, Manage, Engage) by Regina Lutrell. However, in its implementation, several stages have not been implemented optimally, such as at the Share stage, especially at the connect point in terms of communication and interaction through the comment’s column and direct messages. Likewise, at the Optimize stage, especially at the Listen & Learn point, where @beraucoal.id has not been fully optimal in listening, monitoring, and responding through the mention feature on Instagram. By improving and optimizing these two stages, @beraucoal.id Instagram content management can be more effective in increasing engagement and strengthening the company's positive image on social media.